(untitled) (Research, Society and Development, 2024)
The relationship between pressure, velocity and position relative to a fluid in free flow is debited by the Bernoulli equation. Despite its restrictions, this theorem has applicability in the practical teaching of fluid mechanics through the free jet experiment. Therefore, this study aimed to evaluate the applicability of an adaptation to the model made in the laboratory, using a pet bottle and a YF-S201 flow sensor, together with an Arduino UNO board. The leakage of the flow was made through the experimental calculation and the results obtained by the sensor when the water reached an equilibrium height in the bottle. Eighteen height and flow values ​​were collected. The experimental rate found for the height of 15.6 cm (2.06 L / min) was the closest to the value marked on the sensor, 2.01 L / min. The greatest divergence of data occurred for heights below 6.2 cm. This was attributed to the low precision of the YF-S201 sensor and for small heights the error produced was higher. However, the collected data were acceptable, given that standard dissipation of 0.54 L/min. Thus, the adapted flow measurement model can be implemented in remote teaching of engineering disciplines.